If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4x + -9) + 3 = -12x + 30 Reorder the terms: -3(-9 + 4x) + 3 = -12x + 30 (-9 * -3 + 4x * -3) + 3 = -12x + 30 (27 + -12x) + 3 = -12x + 30 Reorder the terms: 27 + 3 + -12x = -12x + 30 Combine like terms: 27 + 3 = 30 30 + -12x = -12x + 30 Reorder the terms: 30 + -12x = 30 + -12x Add '-30' to each side of the equation. 30 + -30 + -12x = 30 + -30 + -12x Combine like terms: 30 + -30 = 0 0 + -12x = 30 + -30 + -12x -12x = 30 + -30 + -12x Combine like terms: 30 + -30 = 0 -12x = 0 + -12x -12x = -12x Add '12x' to each side of the equation. -12x + 12x = -12x + 12x Combine like terms: -12x + 12x = 0 0 = -12x + 12x Combine like terms: -12x + 12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 4y-2=y+10 | | (3/10)x+(2/5)=(-4) | | 0.14(y-5)+0.02y=0.20y-0.5 | | X-14=5x+12 | | 3/10x+2/5=-4 | | y=-5/4x+27.5 | | 8-y=6 | | (3y+12)+(y+12)+41=0 | | 2(x+6)+7=19 | | 3(3w+5)=6(w-1) | | 12r-14=5(2-r) | | (z^2/6)-(z/2)-45=0 | | -9=63 | | 2(x+3)=x-9 | | -5m+12-3(m-3)=8m-(9m-2)-3m+3 | | 9x+2x-14+2=8 | | 13x^2+12x-1=0 | | 3x(6-9)= | | -(x-7)=3x | | 36x^2-(1/81) | | 2x-8=9x+4 | | -2+29-9(m-1)=9m-(8m-7)-3m+4 | | -6-9p=3p | | 12mn-30m-10n+25=0 | | 8(2x+4)=-5 | | 6a^3-2a=a^6 | | .4x-1.3x+14=-4 | | 8x+9=21 | | 9w=5w-12 | | 15+2x=3(x-9) | | a^2+2a+26=0 | | 5=k/3 |